Rumen perforation caused by horn injury in two cows. Issue 1 (December 2015) - Braun, Ueli; Gerspach, Christian; Stettler, Manuela; Grob, Daniela; Sydler, Titus
Abstract Post-operative complications of trocarisation and rumenotomy are the most common causes of peritonitis associated with a rumen disorder. Since horn injury leading to rumen perforation has not previously been reported in the literature, two cows with this condition are reported. Small superficial skin lesions were observed in one of the cows and the other had a perforating skin lesion in the left abdomen. Both cows had signs of hypovolaemic shock. Ultrasonography revealed hypoechoic fluid, echoic lesions and occasional fibrinous septa caudoventral to the reticulum. Caudally the fluid extended to the left flank fold and occupied about one third of the peritoneal cavity. The area of the skin perforation in the left abdomen was swollen and the muscle layers could not be differentiated using ultrasonography. Diffuse fibrino-purulent peritonitis was diagnosed in both cows, and because of a poor prognosis, they were euthanased and necropsied. Perforation of the abdominal wall and rumen with diffuse fibrino-purulent peritonitis was present. Ultrasonography is a suitable tool to characterise the inflammatory lesions between the rumen and left abdominal wall and objectify the interpretation of clinical findings. Horn injury should be included in the rule outs for cattle with left abdominal skin wounds and diffuse peritonitis.